The Effect of Tiktok on Students’ Speaking Ability in Ninth Grade of SMP Swasta Cinta Rakyat 3 Pematangsiantar - Ramindo Rini Sari Simanjuntak; Bernieke Anggita Ristia Damanik; Asima Rohana Sinaga (The Future of Education Journal, 2024)
This study aims to know the effect of using TikTok as a learning medium on students' speaking ability. With the growing popularity of this social media application, the potential of TikTok as a learning media in improving students' speaking skills is an important concern. The research method used is a quasi-experiment with two classes, namely the experimental class using TikTok and the control class using conventional learning medium. The samples in this study were class IX B consisted 31 students as the experimental class and IX C consisted 31 students as the control class, with a total of 62 students. Data were collected through speaking tests conducted before (pre-test) and after the intervention (post-test). The David P. Harris' speaking assessment rubric was used in this research, which includes several aspects namely pronunciatin, grammar, vocabulary, fluency and comprehension. The results of data analysis showed that there was a significant improvement in the speaking ability of students who used TikTok compared to the control group. The researcher found that the mean score in the experimental pre-test was 63.22 and the post-test mean was 77.08 while in the control class pre-test mean was 62.03 and the post-test mean was 73.29. The result of t-test was 2.731 which was higher than t-table at 5% of significance level 2.000.  These findings support the hypothesis that the use of TikTok as a learming media has a significant effect on students' speaking ability in the ninth grade of SMP Swasta Cinta Rakyat 3 Pematangsiantar. This study provides recommendations for educators to consider the use of digital platforms in language learning, as well as paving the way for further research into the use of social media in education.